Use-pattern of oral contraceptive in rural Bangladesh : a case study of Sulla - Chowdhury, Fakhrul Islam; Chowdhury, Ahmed Mashtaq Raza (Bangladesh Bangladesh Institute of Development Studies, 1978)
This paper consists of five sections: section II presents a brief review of the literature, and describes the source and nature of data. section III hints on the characteristics of acceptors and explains the reasons behind pill acceptance.
Includes bibliographical references
II 14/01/2019
Loans
Keywords: Contarceptive drugs; Oral contraceptive; Bangladesh